Analysis of Media and Learning Resources Used by Teachers in the Topic of Direct Current Circuits in Physics - Nurhamdin Putra; Iskandar Zulkarnain; Wandika Wandika; Desnita Desnita; Usmeldi Usmeldi (Universitas Lambung Mangkurat, 2024)
This study aims to analyze the media and learning resources used in 6 public and private high schools to explain the 12th-grade Physics material of Direct Current (DC) circuits and to analyze the media and learning resources with the potential for development in teaching Physics, particularly in the topic of DC circuits, in these six schools. The research employed a quantitative descriptive method with a survey approach, and the instrument used was a questionnaire. The data were obtained from the distribution of questionnaires, with 282 respondents from 6 different schools. The collected data were analyzed by calculating the percentage of media and learning resources used by the six schools. The results showed that the learning media with the highest percentage is